Study guides

☆☆

More answers

-3(n plus 5)12 = -36(n + 5) = -36n - 180

Q: -3(n plus 5)12

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

5n = 2n + 3n .

12m + 3n - 6m + 7n6m + 10n

8m + 3n - 5m + 10n = 3m +13n

3n

Related questions

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

3n+2+3n+2=6n+4

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.

No. 3n is not a factor of 3n + 7.

No. 3n is not a factor of 3n + 7.

3n+5n=8n

5n = 2n + 3n .

is 3n +5 !

12m + 3n - 6m + 7n6m + 10n

No. 3n isn't a factor of 3n + 7. The GCF of 3n + 7 and 9n is 1.

n2-3n+2

3n + 6 = n + 202n = 14n = 7

People also asked

Featured Questions